2012
DOI: 10.1111/jph.12025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ‘Candidatus Phytoplasma solani’ Associated with Tree Peony Yellows Disease in China

Abstract: Tree peony (Paeonia suffruticosais) plants with yellowing symptoms suggestive of a phytoplasma disease were observed in Shandong Peninsula, China. Typical phytoplasma bodies were detected in the phloem tissue using transmission electron microscopy. The association of a phytoplasma with the disease was confirmed by polymerase chain reaction (PCR) using phytoplasma universal primer pair R16mF2/R16mR1 followed by R16F2n/R16R2 as nested PCR primer pair. The sequence analysis indicated that the phytoplasma associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…‘ Ca . P. solani ’ is endemic in Europe and infects a wide range of weeds and cultivated plants reviewed in [68–72]. Our data are consistent with a model in which phytoplasma competes for Fe and perturbs the long-distance signalling of Fe status that is transmitted to the roots.…”
Section: Introductionsupporting
confidence: 86%
“…‘ Ca . P. solani ’ is endemic in Europe and infects a wide range of weeds and cultivated plants reviewed in [68–72]. Our data are consistent with a model in which phytoplasma competes for Fe and perturbs the long-distance signalling of Fe status that is transmitted to the roots.…”
Section: Introductionsupporting
confidence: 86%
“…The symptoms were similar to the symptoms of tree peony yellows disease (Gao et al. ). Phytoplasma‐like bodies were observed in the sieve elements of the phloem tissues of symptomatic camellia (Fig.…”
Section: Resultssupporting
confidence: 75%
“…In 2012, camellia plants with symptoms of yellowing, which was similar to the symptoms of tree peony yellows disease (Gao et al. ), were observed in Tai'an in Shandong province, China. The objective of this study was to confirm that camellia yellows disease is associated with a phytoplasma infection.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…P. phoenicium’-related strain infecting blueberry plants, which previous studies showed to be typically infected by ‘ Ca . P. asteris’ causing blueberry bushy stunt disease (BbSP) (Pérez-López et al 2019; Arocha-Rosete et al 2019; Hammond et al 2021). However, blueberry plants have been reported infected by ‘ Ca .…”
mentioning
confidence: 99%